Isotope effects induced by the action of ions on the surface of solids; Technical Physics; Vol. 55, № 3 - Nikitenkov N. N. (2010, 2010)
We report on the results of study of isotope effects induced in solids by ion sputtering and ion implantation. The experiments are carried out using secondary ion mass spectrometry and secondary ion energy-mass spectrometry on molybdenum and copper-implanted nickel samples, as well as a number of titanium modifications. General regularities are revealed in the variation of the isotope composition in various processes. The mechanisms of isotope effects are discussed.